Pentingnya Pengenalan Permainan Tradisional dalam Menanamkan Nilai Karakter dan Budaya - Dinar Ayu Mirunggan Sari; Dwi Kurniawan (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2024)
Traditional games play a crucial role in enriching character values and culture among children. In this paper, the involvement of traditional games in fostering social interaction, strengthening cultural identity, and shaping children's characters is explored extensively. Despite the rapid advancement of technology shifting the popularity of modern games, traditional games still hold irreplaceable values. Through the analysis of various traditional games such as hide and seek, tag, hopscotch, stilts, and fortresses, values like honesty, teamwork, responsibility, and patriotism are identified as integral parts of children's play experiences. This research emphasizes the importance of introducing traditional games in the context of character education, considering their role in shaping personalities and reinforcing cultural identities. Through a descriptive qualitative approach, this study delves into the depth of values embedded in traditional games and highlights the urgency of preserving this cultural heritage amidst globalization. The research findings indicate that traditional games not only provide entertainment but also serve as effective learning tools in shaping children's characters. Therefore, efforts to promote and introduce traditional games to children are crucial in maintaining the continuity of cultural heritage and fostering positive values in society.